METHODOLOGIC APPROACH TO ASSESSING THE QUALITY OF SERVICES PROVIDED IN THE OPTIMIZATION OF CUSTOMS SERVICES - Nigmanov Erkin Abdulmugnievich; Lutfullaev Shukrullo Qudratillaevich; Sodikov Islombek Isakali ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the concept of customs services, the factors that significantly affect its quality, the main criteria for quality indicators of customs services, as well as the methodology for assessing the quality of customs services.